Dampak Job Insecurity dan Job Stres terhadap Turnover intention: Peran Mediasi Kepuasan Kerja di Bank Muamalat Yogyakarta - Fauzi, Ali; Jauhari, Fiki Afif; Suhada, Suhada (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to evaluate the influence of job insecurity and job stress on Turnover intention through job satisfaction as an intervening variable among employees of PT. Bank Muamalat branch in Yogyakarta. A total of 36 employees were selected as samples using the simple random sampling method. The analysis was conducted using Structural Equation Modeling (SEM) measurements in Smart PLS 3.2.9. The test results indicate that job insecurity has a positive and significant impact on Turnover intention, while it does not have a positive and significant impact on job satisfaction. Job stress has a positive and significant impact on Turnover intention but does not have a positive and significant impact on job satisfaction. Job satisfaction has a negative and significant impact on Turnover intention. Additionally, job insecurity and job stress have a positive and significant impact on Turnover intention through job satisfaction as an intervening variable.